2010
DOI: 10.1063/1.3472978
|View full text |Cite
|
Sign up to set email alerts
|

Electronic absorption and phosphorescence of cyanodiacetylene

Abstract: Electronic absorption and emission spectra have been investigated for cyanodiacetylene, HC(5)N, an astrophysically relevant molecule. The analysis of gas-phase absorption was assisted with the parallel rare gas matrix isolation experiments and with density functional theory (DFT) predictions concerning the excited electronic states. Mid-UV systems B (1)Delta<--X (1)Sigma(+) (origin at 282.5 nm) and A (1)Sigma(-)<--X (1)Sigma(+) (306.8 nm) were observed. Vibronic assignments have been facilitated by the discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 28 publications
10
58
0
Order By: Relevance
“…The solid infrared bands are usually more intense than for molecules trapped in argon matrix, which facilitated the detection of combinations modes and overtones. Some of these infrared bands are assigned by comparison with the gaseous spectrum and previous experiments (Benilan et al 2007;Coupeaud et al 2008;Turowski et al 2010). The other ones are tentatively assigned in this paper (Table 2).…”
Section: Infrared Spectrum Of Hc 5 Nmentioning
confidence: 81%
See 1 more Smart Citation
“…The solid infrared bands are usually more intense than for molecules trapped in argon matrix, which facilitated the detection of combinations modes and overtones. Some of these infrared bands are assigned by comparison with the gaseous spectrum and previous experiments (Benilan et al 2007;Coupeaud et al 2008;Turowski et al 2010). The other ones are tentatively assigned in this paper (Table 2).…”
Section: Infrared Spectrum Of Hc 5 Nmentioning
confidence: 81%
“…The cyanodiacetylene is known to absorb in the near ultraviolet at 353 nm (Fisher & Ross 2003). From the phosphorescence measurements, the lowest triplet state (T 1 ) of HC 5 N is located at ∼424 nm and we expect (vide infra) singlet-triplet absorption at >300 nm to be amplified due to solid-state effect (Gudipati 1994;Turowski et al 2010). We have not found to date any report of the photochemical formation of HC 5 N polymer, and our study reported here is the first observation of such polymerization under simulated Titan's lower atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The main vibronic progressions concern the mutually similar vibrations n 1 o f N C 4 N and n 2 of HC 5 N [10].…”
Section: Resultsmentioning
confidence: 99%
“…Its IR and Raman vibrational spectroscopy was thoroughly studied [2][3][4][5], as were the mid-UV [6,7] and vacuum-UV [8] electronic transitions. Electronic luminescence (phosphorescence) has so far been found for several cyanoacetylene-family molecules dispersed in solid rare-gas matrices, namely for NC 4 N [9] and HC 5 N (cyanodiacetylene) [10], for another isoelectronic pair: NC 2 N (cyanogen) [11] and C 3 N -(cyanoacetylide anion) [12], and finally for NC 6 N [13]. Such emission, on the other hand, is not occurring for HC 3 N (cyanoacetylene).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation